Dirac Particles Emission from An Elliptical Black Hole - Yuant Tiandho (Universitas Pendidikan Indonesia, 2017)
According to the general theory of relativiy, a black hole is defined as a region of spacetime with super-strong gravitational effects and there is nothing can escape from it. So in the classical theory of relativity, it is safe to say that black hole is a